Cementing regional integration or building walls? Competition, cartels and regional integration in the cement industry in Africa. (5th December 2022) - Roberts, Simon; Simbanegavi, Witness; Vilakazi, Thando
Abstract: The cement industry requires large‐scale energy and capital‐intensive plants, ideally located close to limestone deposits. These characteristics mean that there are substantial gains which can be realised from regional trade and competition in this inherently oligopolistic industry. This article analyses competition and trade in cement in Southern and East Africa. It considers how competition and coordination, new entry and competition enforcement have affected cross‐border trade and domestic prices in the countries of the East African Community and Southern African Development Community. We find that gains from trade through increased competition did not occur without there also being new entry to disrupt the incumbent firms which operated across the region. Entry at scale to supply regional markets led to substantial reductions in prices from the competition, in line with international studies of the effect of the cement cartels. The article points to the importance of prioritising competition enforcement as part of regional integration.